Konsep Pengembangan Ekonomi Kerakyatan di Kota Medan - M.Umar Maya Putra (Lembaga Penelitian & Pengabdian pada Masyarakat (LPPM) Universitas Mikroskil, 2015)
By 2012 the population of Medan has applied the concept of community empowerment. National Program for Community Empowerment (PNPM) adapted from the central government into a program that is often done to improve community empowerment. Other programs also do is increase the entrepreneurial base that always emphasized with some assistance such as Credit (KUR) and Revolving Fund Program (GDP) to drive the real sector which is the base that reaches directly to the public. But in a dilemma, Medan is still recorded a maximum point in the development of industry. If ordered three of the Central Bureau of Statistics in 2012, the Regional North Sumatra contributor who has contributed in the industry sector is 1. Deli Serdang amounted to 29.95%, 2 Medan of 18, 20%, and the 3. Batu Bara for 13.75%. From the data collected, of course, required an increase of the industrial sector to accelerate a multiplier effect on revenue (PAD) and empower a more populist economic base can be carried out and the public is able by itself to have independence and can develop an invention and innovation of a concept superior product as a brand in Medan.